IMPLEMENTASI METODE PRAKTIKUM BERBASIS LINGKUNGAN PADA MATERI REAKSI KIMIA SISWA KELAS X MADRASAH ALIYAH AL JIHAD NANGA TEPUAI KAPUAS HULU - Linlin Suryadi; Elin B Somantri; Rizmahardian Azhari Kurniawan (Universitas Muhammadiyah Pontianak, 2017)
ABSTRACTThe students practicial work in Madrasah Aliyah Al Jihad does not have laboratories facilities and infrastructures still minimal. It be over come by using simple tools and simple materials within students evironment and ussually encontered in everyday. In this research the result of the study before and after implementation practicial work based learning will be analyzing. This reasearch was conducted on to students by using pre- experimental research and one group pretest-posttest design. The subject in this research were students of class X Madrasah Aliyah Al Jihad. This research was condacted three phases: Preparation imlementation and data analysis, the data were collected by using the test (Pretest and Posttest) observation, and interviews. The everage value pretest is 38.00 and 74,00 for posttest. The data pretest and postest were analyzed by using T test which assuming variance test was not homogeneous. T test result by using pretest and posttest is different in significant. The imlpementation method lab-based enveronment can be improve student`s learning outcome. The students participate actively in teaching learning process.Keywords: Learning outcome, Lab-based environment method